Since y= x+1 in the first equation,substitutex+1 for y in the second equation: y= x+ 1= 2x- 4. Now solve x+ 1= 2x-4 for x and then use y= x+1 to get x.

??? This is the same pair of equations!y=x+1

y=2x-4

Adding the two equationsSolve the linear systems using elimination

6x+3y=27

-6x+2y=-2eliminatesx:

(6x+ 3y)+ (-6x+ 2y)= 27+ (-2)

(6x- 6x)+ (3y+ 2y)= 27- 2

5y= 25

Solve for y and then replace y by that number in either equation to find x.

4x+3y=21

4x-5y=29Subtractone equation from the other:

(4x+3y)- (4x-5y)= 21- 29

(4x- 4x)+ (3y-(-5y)= 21- 29

8y= -8.

Could someone please explain substitution and elimination for me, thanks for your help.